HUBUNGAN PERSEPSI YANG MEMPENGARUHI PENGGUNAAN TECHNOLOGY ACCEPTANCE MODEL DENGAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN ELECTRONIC HEALTH RECORDS DI RS MOH RIDWAN MEURAKSA JAKARTA - Syafitri Nurarkhabi Tsabitah (2023)
The documentation of nursing care is an important activity in nursing practice. Electronic Health Records (EHR) has become a more efficient solution for documenting nursing care. The purpose of this study was to determine the relationship between the perception of the use of TAM / (Technology Acceptance Model) with the documentation of nursing care with the Electronic Health Records (EHR) method in the inpatient room. This study used a descriptive correlation research design using a cross sectional approach. The sampling technique used was total sampling with 71 nurses as respondents. Data collection using a questionnaire and analyzed using the Spearman-Rho test. The statistical test results show that there is a strong relationship between the perception of the use of TAM (Technology Acceptance Model) (ρ = 0.533) with electronic health records nursing care documentation. Length of service, level of education, and marital status had a moderately strong relationship with Electronic Health Records nursing care documentation. The conclusion of this study is that there is a significant relationship between TAM (Technology Acceptance Model) factors and electronic health records (EHR) nursing care documentation. The results of this study are expected to be used as a basis for improving effective and efficient nursing care documentation through the use of EHR. By knowing these factors, health practitioners and hospital management can improve their understanding of the challenges and opportunities associated with using EHR in nursing care documentation.